2022
DOI: 10.3390/cancers14163996
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Resistance to HER2-Directed Therapies in Breast Cancer

Abstract: Human epidermal growth factor receptor 2 (HER2)-positive breast cancer accounts for around 15% of all breast cancers and was historically associated with a worse prognosis compared with other breast cancer subtypes. With the development of HER2-directed therapies, the outcomes of patients with HER2-positive disease have improved dramatically; however, many patients present with de novo or acquired resistance to these therapies, which leads to early recurrences or progression of advanced disease. In this narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 115 publications
(176 reference statements)
1
25
0
2
Order By: Relevance
“…However, and despite all the advancements in this field, many patients still suffer from recurrences and disease progression on treatment, suggesting that tumors can develop resistance to these therapies. Furthermore, a growing body of evidence shows that the vast majority of patients do not respond to these therapies, and those who initially respond eventually develop resistance to treatment [ 144 , 145 , 146 ]. This is particularly relevant in the case of trastuzumab, as studies have indicated that the majority of patients who respond to treatment based on trastuzumab acquire resistance within a year.…”
Section: Mechanisms Of Resistance To Her2-targeted Therapiesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, and despite all the advancements in this field, many patients still suffer from recurrences and disease progression on treatment, suggesting that tumors can develop resistance to these therapies. Furthermore, a growing body of evidence shows that the vast majority of patients do not respond to these therapies, and those who initially respond eventually develop resistance to treatment [ 144 , 145 , 146 ]. This is particularly relevant in the case of trastuzumab, as studies have indicated that the majority of patients who respond to treatment based on trastuzumab acquire resistance within a year.…”
Section: Mechanisms Of Resistance To Her2-targeted Therapiesmentioning
confidence: 99%
“…Since HER2 is involved in a range of biological processes such as proliferation, survival, angiogenesis, and metastasis, resistance to HER2-targeted therapies can develop due to various mechanisms. A deeper understanding of these mechanisms, as well as the possible strategies to overcome them, will help improve the outcomes for patients with HER2-positive cancers [ 144 , 147 ]. Table 3 outlines the mechanisms of resistance to HER2-targeted therapies with the suggested strategies to overcome it.…”
Section: Mechanisms Of Resistance To Her2-targeted Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several classes of HER2-targeted agents have been developed for the treatment of HER2-positive (HER2+) breast cancer, including monoclonal antibodies (Trastuzumab and Pertuzumab), small molecule tyrosine kinase inhibitors (Lapatinib and Neratinib) and antibody-drug conjugates (trastuzumab emtansine T-DM1) [2,3]. Although the outcomes of patients with HER2-positive disease have improved dramatically, the diseases will inevitably relapse because of de novo or acquired resistance to HER2-targeted therapies [4]. How to improve the therapeutic e cacy to relapse patient remains an urgent problem to be solved.…”
Section: Introductionmentioning
confidence: 99%